GLOBAL TRENDS AND THE THERMAL ENERGY CAPACITIES GREATER THAN 10 MW IN SLOVENIA - Strušnik, Dušan (Journal of Energy Technology, 2024)
Thermal energy is the most significant form of energy production and is of key importance for satisfying global energy needs. When combusting primary fuel in thermal power stations, environmentally dangerous greenhouse gases are released as a consequence of obtaining electrical and thermal power. Strict environmental energy legislation requires thorough changes to thermal power stations. This paper analyses global, European and Slovene trends of the consumption of primary sources (coal, natural gas, etc.) and the adjustment of thermal power stations to energy needs and environmental legislation. Two anticipated scenarios (Basic and Blue) of trend flows are discussed, and guidelines are given. Thermal energy facilities, development guidelines and the energy dependences of Slovenia will be presented.